Anti-leishmania antibodies in cerebrospinal fluid from dogs with visceral leishmaniasis - Lima, V.M.F. [UNESP]; Gonçalves, M.E. [UNESP]; Ikeda, F.A. [UNESP]; Luvizotto, M.C.R. [UNESP]; Feitosa, M.M. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2003)
Visceral leishmaniasis in Brazil is caused by Leishmania (Leishmania) chagasi and the dog is its most important reservoir. The clinical features in dogs include loss of weight, lymphadenopathy, renal failure, skin lesions, fever, hypergammaglobulinemia, hepatosplenomegaly, anemia, and, rarely, neurological symptoms. Most infected animals develop active disease, characterized by high anti-leishmania antibody titers and depressed lymphoproliferative ability. Antibody production is not primarily important for protection but might be involved in the pathogenesis of tissue lesions. An ELISA test was used to determine if there is an association between neurological symptoms and the presence of anti-L. chagasi antibodies in cerebrospinal fluid (CSF). Thirty serum and CSF samples from symptomatic mixed breed dogs (three with neurological symptoms) from a region of high incidence of visceral leishmaniasis in Brazil were examined for antibody using total parasite antigen and anti-dog IgG peroxidase conjugate. A high level of L. chagasi antibodies was observed in sera (mean absorbance ± SD, 1.939 ± 0.405; negative control, N = 20, 0.154 ± 0.074) and CSF (1.571 ± 0.532; negative control, N = 10, 0.0195 ± 0.040) from all animals studied. This observation suggests that L. chagasi can cause breakdown of filtration barriers and the transfer of antibodies and antigens from the blood to the CSF compartment. No correlation was observed between antibody titer in CSF and neurological symptoms.
Keywords: Leishmania (Leishmania) chagasi; Visceral leishmaniasis; Cerebrospinal fluid; Dogs; Antibodies